You Look Pretty Happy: Attractiveness Moderates Emotion Perception - Lindeberg, S.; Craig, Belinda; Lipp, Ottmar (American Psychological Association, 2018)
© 2018 American Psychological Association. A happy face advantage has consistently been shown in emotion categorization tasks; happy faces are categorized as happy faster than angry faces as angry. Furthermore, social category cues, such as facial sex and race, moderate the happy face advantage in evaluatively congruent ways with a larger happy face advantage for more positively evaluated faces. We investigated whether attractiveness, a facial attribute unrelated to more defined social categories, would moderate the happy face advantage consistent with the evaluative congruence account. A larger happy face advantage for the more positively evaluated attractive faces than for unattractive faces was predicted. Across 4 experiments participants categorized attractive and unattractive faces as happy or angry as quickly and accurately as possible. As predicted, when female faces were categorized separately, a happy face advantage emerged for the attractive females but not for the unattractive females. Corresponding results were only found in the error rates for male faces. This pattern was confirmed when female and male faces were categorized together, indicating that attractiveness may have a stronger influence on emotion perception for female faces. Attractiveness is shown to moderate emotion perception in line with the evaluative congruence account and is suggested to have a stronger influence on emotion perception than facial sex cues in contexts where attractiveness is a salient evaluative dimension.